COMPONENTA NARATIVĂ A IDENTITĂȚII POLITICE LA PAUL RICŒUR - Stuparu Lorena (Revista de Știinţe Politice şi Relaţii Internaţionale, 2024)
In this paper I will refer to two composite and complex notions, narrative identity and political identity, which represent not only fundamental theoretical notions, but also components of an action that, integrated in the culture of dialogue, could lead to peace and balance in today’s world. The political identity – narrative identity distinction can be found both at the level of the individual (schematizing, the citizen has a political identity, the person has a narrative identity) and at that of society, if we accept on the one hand, that the basic meaning of the notion of political identity refers primarily to the citizens of a state (because starting with modernity, the free individual has power and political identity) or to certain groups organized on political criteria, and on the other hand that this notion also has the collective meaning of national-state identity, respectively cultural, which interacts both in content and form with that of civic identities. And because between the two composite notions, beyond the differences, there is above all cohesion, i.e. narrative identity contributes to the configuration and definition of political identity, just as political identity can represent a chapter or an important moment in a story, from a history, I will focus on the contribution of the narrative identity to the definition of the political identity, having as a theoretical reference the contribution of Paul Ricœur in this matter, because Ricœur’s political philosophy shows us how to read and interpret what happens to man not only as an amount of ever-changing data, more or less accurate, as a more or less significant statistic, but also as a meaningful story.